Space Technology Applications for Water Quality in Sustainable Development - Oluwafemi, F. A.; Olubiyi, R. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Water is one of the most important elements for sustaining-life. Despite water’s abundance, good quality water is available in a very limited quantity. Water quality describes water’s condition, including physical, chemical, biological and radiological-characteristics, usually with respect to its suitability for a particular purpose such as drinking, swimming and irrigation. Many factors can reduce quality of water such as water-pollution which is the contamination of water-bodies, usually resulting from human-activities. Poor water quality poses a health-risk for people and ecosystems. Water quality is measured by several factors, examples of which are the dissolved-oxygen, salinity, turbidity, pH, temperature. Water quality is a complex issue and requires large amounts of diverse accurate data in a timely manner. Collection of water quality measurement data by traditional method can be quite difficult and resource intensive especially in the remote-areas. Therefore, there is a need to supplement the traditional method of ground-based monitoring with space technology especially satellite-based monitoring that provides better effective means of data-collection. Satellite-based monitoring is helpful in attaining sustainable development, which includes economic-growth, environmental-protection and social-equality; in-line with the Sustainable Development Goal “Clean Water and Sanitation” of the United-Nations. Space technology applications for water quality has several advantages including large area coverage, measurement-frequency, effective up-to-date, cost-effective and in time manner. This paper reviews space technology’s use in water quality assessment to achieve sustainable development. Examples of space technology spin-offs and use of on-line open data-access on water quality monitoring are discussed. It also proposes satellite technology viewing few millimeters contaminants in water-bodies in the nearest-future.